2016
DOI: 10.1016/j.cub.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glucose Transport into Neurons Rescues Aβ Toxicity in Drosophila

Abstract: . Electrical hyperexcitation of lateral ventral pacemaker neurons desynchronizes downstream circadian oscillators in the fly circadian circuit and induces multiple behavioral periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 0 publications
6
31
0
Order By: Relevance
“…The effect of Wnt3a treatment was significant after 15 s of exposure, and the time-dependent effect was blocked by co-incubation with Dkk1. The IC 50 value was similar to the values reported for GLUTs. The effect of Wnt3a was independent of both transcription and synaptic effects of Wnt3a and was blocked by co-treatment with Dkk1, AZD5363, and TCS183.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The effect of Wnt3a treatment was significant after 15 s of exposure, and the time-dependent effect was blocked by co-incubation with Dkk1. The IC 50 value was similar to the values reported for GLUTs. The effect of Wnt3a was independent of both transcription and synaptic effects of Wnt3a and was blocked by co-treatment with Dkk1, AZD5363, and TCS183.…”
Section: Discussionsupporting
confidence: 77%
“…2A). We found that the IC 50 value of the effect of Cyt B on the uptake of [2-3 H]DG was 0.70 Ϯ 0.06 M. This finding is consistent with glucose transport through GLUTs (31) (Fig. 2A) 6 cells.…”
Section: Effects Of the Acute Wnt3asupporting
confidence: 79%
“…It has been demonstrated that the exogenous stimulation of the glucose metabolism can rescue the cognitive performance in AD patients (Baker et al 2011;Craft et al 2012;Parthsarathy and Holscher 2013). Likewise, the ability of increased glucose metabolism to improve cognitive performance or rescue neuronal cells against the toxicity of Ab has been described in several model organisms, including mice, rats and Drosophila (Niccoli et al 2016;Liu et al 2017). This further demonstrates the close relationship between the deregulation of cerebral glucose metabolism and the cognitive failures described in AD.…”
mentioning
confidence: 80%
“…With this respect, it is interesting to note that the glucose transporters GluT1 and GluT3 have been reported to be impaired in neurodegenerative diseases such as Huntington's disease (Morea et al, 2017) or Alzheimer 's disease (Mark, Pang, Geddes, Uchida, & Mattson, 1997;Shah, Desilva, & Abbruscato, 2012). More precisely, increased glucose transport is able to rescue a Drosophila model of Ab toxicity (Niccoli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%